PERAN IBADAH DALAM MENGATASI KRISIS IDENTITAS SISWA KRISTEN DI ERA DIGITAL (Studi Kasus di SMA Advent 1 Medan) - Futriana Purba; Imelda Butarbutar; Nurliani Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This thesis was conducted under the supervision of Pdt. Imelda Butar-Butar, S.Th., M.Psi.,M.Pd and Dr. Nurliani Siregar, S.Ag., M.Pd at the Faculty of Teacher Training and Education, HKBP Nommensen University Medan. This study aims to identify and analyze the role of worship in overcoming the identity crisis of Christian students in the digital era, particularly at SMA Advent 1 Medan. The background of this research is based on the increasing phenomenon of identity crisis among adolescents due to the influence of digital media, such as low self-confidence, loss of life direction, declining spirituality, and the emergence of various psychosocial problems. In this context, worship as part of Christian Religious Education has an important role as a means of spiritual development, strengthening self-identity, and providing psychological support for students. This research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results of the study indicate that worship plays a significant role in helping students overcome identity crises in the digital era. Through elements of worship such as prayer, Bible reading, reflection, and praise songs, students experience spiritual strengthening, increased self-awareness, and the formation of a stronger spiritual identity. In addition, worship functions as a fellowship that provides social and emotional support, helping students manage psychosocial pressures and the negative influences of digital media.